Kontroversi Penyebaran Hadis Amalan Khusus Bulan Rajab di Media Sosial Instagram Pada Tahun 2023 - Rafli Fadhilla Akhmad; Muhammad Ilyas (Departement of Mathematics Education, 2023)
The development of the era that social media is needed in everyday life. Of the many social media that exist, Instagram is one of the social media that is most often used by the public. Instagram is currently also used for da'wah where Islamic Study Committees, Ustads, and Muslim communities can use Instagram as a da'wah media to disseminate information in the form of studies, Islamic knowledge in the form of photos and videos that can be utilized for the community. In this case, research was carried out on how many hadiths were spread on Instagram social media and to find out the degree of these hadiths. This research used a qualitative method, through library research, the method of analyzing syarah hadith. From the results of the research, it was found that the hadiths spread on Instagram social media about special practices in the month of Rajab are that the degree of hadith is weak and there is no specific determination of practice in the month of Rajab.